Massive nasal meningoencephalocele in a 4-month-old infant: A case report - Shahin Rajaeih; Farshad Riahi; Sam Mirfendereski (Radiology Case Reports)
A massive nasal meningoencephalocele is a rare congenital anomaly characterized by the herniation of brain tissue and meninges through a defect in the skull base into the nasal cavity. It typically manifests as nasal obstruction and respiratory distress in infancy and is diagnosed via imaging techniques such as magnetic resonance imaging, often necessitating surgical intervention for treatment. This document outlines the endoscopic treatment of a 4-month-old child with a significant nasal meningoencephalocele.